A jurisprudential analysis of the position of the council in legitimizing the election of the Islamic ruler with an emphasis on Ayatollah Khamenei's views - mohammad esmaeil abdollahi (پژوهش‌های فقهی مسائل مستحدثه)
This article examines the role of the council in legitimizing the election of an Islamic ruler from the perspective of Ayatollah Khamenei (may God preserve him) in the religious governance system. The main issue of the research is the role of the council in combining divine and popular legitimacy in the political system of Islam and whether the council can be a basis for the legitimacy of the Islamic government or is merely an aspect of acceptance. The aim of the article is to explain the Supreme Leader’s view on the fundamental role of the council in the objective realization of the Islamic government and to fill the research gap in this field. This research was conducted using a descriptive-analytical method and based on authentic Shiite jurisprudential sources, the Holy Quran, the narrations of the Infallibles (AS), and the statements and rulings of the Supreme Leader. The research findings show that from Ayatollah Khamenei’s perspective, the council is not only a tool for gaining public acceptance but also one of the fundamental pillars of the legitimacy of the Islamic government. He emphasizes the role of the people's vote as a necessary condition for the practical realization of the government and considers the scope of the council to go beyond executive affairs and also includes the election of the ruler at the macro-level of the government. Also, the conditions for the correct realization of the council from his perspective include scientific competence, piety, justice, socio-political insight, efficiency, and adherence to religious values. The results of the research indicate the theoretical innovation of the Supreme Leader in combining religious principles and social requirements, which strengthens the public participation of Muslims, ensures social justice, and prevents the concentration of power.